The Potency of Streptomyces spp. from Shallot Land as Entomopathogen of Onion Caterpillar Pest Spodoptera exigua - Pratista, Ariq Dies; Windriyanti, Wiwin; Suryaminarsih, Penta; Mujoko, Tri; Indrawan, Arga Dwi; Harsiyanti, Harsiyanti (International Journal on Food, Agriculture and Natural Resources, 2025)
Spodoptera exigua is a major pest of shallots (Allium ascalonicum L.), capable of causing up to 100% yield loss if uncontrolled. Streptomyces sp. is a soil-dwelling Actinomycetes bacterium that can be used to control S. exigua. This study aimed to determine the potential of Streptomyces spp. isolates from shallot fields as an entomopathogen against S. exigua. The research employed a Factorial Complete Randomized Design (CRD). The first factor consisted of one Streptomyces spp. isolate obtained from the Pare-Kediri region (BMP) and three isolates from Sidera-Palu (BMS1, BMS2, and BMS3). The second factor was the concentration of the Streptomyces sp. suspension consist of 0%; 5%; 10%; and 15% with three replication per treatment (48 units total). Data on larval mortality and damage intensity were analyzed using RStudio via ANOVA and DMRT (α=5%). The BMP (15%) treatment demonstrated the highest efficacy, achieving 76.67% larval mortality while maintaining the lowest damage intensity of 0.20% on shallot plants. These results highlight BMP isolate at 15% concentration as the most promising biocontrol agent and support its further field evaluation as a sustainable alternative to chemical insecticides.